Racionalidad filosófica y figuras simbólicas - Wunenburger, JEAN-JACQUES (Escritura e Imagen, 2005)
This work pays attention to the debt of abstract rationality to the iconic and symbolic. From a critical perspective towards a philosophy based in the clear and the distinct, this paper tries to connect image and concept. The first section studies the imagery in the formation of philosophical ideas, having in mind thinkers such as Plato, Plotinus and Kant. The second section, titled «The Imaginal Schematism in Thought», adopts a genetic or poietic perspective of the image; which is considered in itself a source of thought. The author proposes an archeology of thought, in which it is not sufficient an analysis based on logical concepts and language. For that reason it will be necessary to turn to a topology, where space will be understood as the form of thought. The rise and unfold of the image, considered as a form of space, will be determinants in the beginning and development of thought. The image of the circle, essential in monist systems, and the image of the mirror, understood as the reflection of the same or like the menacing double, will be discussed as examples that acknowledge the figurative aspect of representations.